ANALYSIS OF THE DIFFERENCE OF GREEN FINANCING APPLICATION OF COMPANY PERFORMANCE PT. AIR ASIA - Berto Berto; Estu Widarwati; Nunik Nurmalasari (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2020)
The purpose of this research is to analyze the implementation of green financing and to find an impact of application of green financing toward earning pt.airasia. Industri activities oftentimes give some bad impact to environment surrounding. Green financing is a Financing or lending to businesses that are environmentally friendly. The implementation of green financial can give good image for the company however preliminary research found not many companies are implementing green financial. This research will use quantitave approach and different test or paired T-test will use for statistical testing, in order to test the research assumptions. Variable of this research are Green financial and Earning. This research is expected will contribute for the development of green financial theory and enhancement of the implementation of green financial especially in airline on Asian Economic community era.